LOW CD 4 COUNT IN HIV NEGATIVE PATIENT-A CASE OF COMMON VARIABLE DEFICIENCY CENTRAL HOSPITAL NWR JAIPUR DEPT OF MEDICINE: A CASE REPORT - MEENA, RAKESH KUMAR; AGARWAL, DEEPAK; PABRI, MANISH (International Journal of Current Pharmaceutical Research, 2024)
Common variable immunodeficiency syndrome (CVID) is a disorder characterised by reduced levels of IgG, IgA and/or IgM, and recurrent bacterial infections. Sinopulmonary infections, gastrointestinal infections. It is commonly seen in association to immunodeficiency states such as CVID, IgA deficiency and chronic infections due to Giardia lamblia and Helicobacter pylori. We report a case of CVID with low CD 4 counts having recurrent diarrhoea, weight loss, anasarca and Hypoproteinaemia.